About The Reasons For The Distinctive Role Of Kutaisi In The Linguistic-Cultural State In The History Of Georgia - Putkaradze, Tariel (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2018)
Kutaisi has been the center of Georgian culture and spirituality from ancient times. Such a role and function was determined by several factors in the history of the Georgian nation: The country of Kutaisi (Old Ingrid, Mokhiris; Imereti) was fully protected by outer Georgian parts: - To the north by the Caucasus Mountains, whose passages were controlled by Georgians from Svaneti or Racha-Lechkhumi; - In the south, Georgian Meskhetians guarded the territory; - To the east - Kartlians; - From the west - the sea. Accordingly, gifted Georgians living in this part of central Georgia had more time and disposition for the development of creative thinking and culture. Such geographical location defined the special role of Kutaisi, and many facts emphasizing Kutaisi’s unique historical role. For centuries Kutaisi has been the theological and royal center of Georgia; Consequently, the Georgian intellectual elite gathered here. This part of Georgia was rarely conquered by a foreign enemy, which defined the continuous and irreversible development of literary culture, and culture in general. In the modern demographic and economic crisis, when talented youth are flowing out of Kutaisi, the greatest challenge for Kutaisi is to maintain a national-level Georgian-language center. Building a university for 60,000 foreign-language students and opening foreign-language enclaves in Kutaisi will certainly not be a benefit for the city. If we do not plan the future of Kutaisi, we will soon drain the “country of Kutaisi” in the modern global world, As a pure source of Georgian consciousness and Georgian culture; a source that has survived to this day for its natural geographical protection. In modern conditions, the natural barriers (the Caucasus, the sea, the surrounding Georgian parts) no longer work: in the age of the Internet and missiles, guarding of neighbors or the Caucasus range can no longer be considered as the natural protective barrier; In modern conditions, the protective “edge” should be Georgian-language science, Georgian-language culture, and generally Georgian-language consciousness. Accordingly, it is necessary for both the central government of Georgia and the political spectrum in Kutaisi to clearly understand the traditional and indispensable role of Kutaisi for the Georgian state and Georgian culture, Accordingly, take into account the historical function of Kutaisi, plan the cultural and educational-scientific life of the city.